Kerja Harmoni Zat Gizi dalam Meningkatkan Imunitas Tubuh Terhadap Covid-19: Mini Review - Sri Sumarmi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
ABSTRACTBackground: The Covid-19 pandemic in Indonesia has been running since March 2020. Efforts to break the chain of transmission of the disease caused by the new SARS-CoV 2 coronavirus are by avoiding contact by practicing social & physical distancing and improving personal hygiene, and increase immunity or body defense against the corona virus.Purpose: This article discusses the role of macro nutrients and micronutrients that have the potential to increase immunity such as omega-3 fatty acids, several water soluble vitamins such as vitamin B6, vitamin C, as well as fat soluble vitamins such as vitamin A, vitamin D and vitamin E. as well as several minerals such as Fe, Zn, Se. The mechanisms of innate immunity and adaptive immunity that involve these nutrients will be discussed in depth, as well as how the cellular mechanism fights the corona virus.Discussion: The mechanism for the entry of the corona virus into the cell is through a mechanism called endocytosis, in which the virus is captured by the receptors on the surface of the cell, then drawn into the cell. Spike protein (protein S) facilitates the entry of viruses into target cells, especially lung cells.Conclusion The body's defense mechanisms against the corona virus are: 1) strengthening the body's frontline defenses or innate immunity; 2) stimulates the production of IgM and IgG immunoglobulins in the circulation; 3) blocking the virus from binding to the ACE-2 receptor; 4) reduce the intensity of cytokine storms; 5) reduce the speed of virus replication. ABSTRAKLatar Belakang: Pandemi Covid-19 di Indonesia telah berjalan sejak bulan Maret 2020. Upaya untuk memutus rantai penularan penyakit yang disebabkan oleh virus corona jenis baru SARS-CoV 2 adalah dengan menghidari kontak dengan cara mempraktekkan social & physical distancing dan meningkatkan kebersihan diri, serta meningkatkan imunitas atau pertahanan tubuh terhadap virus corona. Tujuan: Artikel ini membahas peran zat gizi makro dan zat gizi mikro yang berpotensi untuk meningkatkan imunitas seperti asam lemak omega-3, beberapa vitamin larut air seperti vitamin B6, vitamin C, juga vitamin larut lemak seperti vitamin A, vitamin D dan vitamin E, serta beberapa mineral seperti Fe, Zn, Se. Mekanisme innate immunity dan adaptive immunity yang melibatkan zat gizi tersebut akan dibahas secara mendalam, serta bagaimana mekanisme selular melawan virus corona. Ulasan: Mekanisme masuknya virus corona ke dalam sel adalah melalui mekanisme yang disebut endositosis, yaitu virus ditangkap oleh reseptor yang terdapat di permukaan sel, kemudian ditarik masuk ke dalam sel. Spike protein (protein S) bertugas memfasilitasi masuknya virus ke dalam sel target, terutama sel paru.Kesimpulan Mekanisme pertahanan tubuh melawan virus corona adalah: 1) menguatkan pertahanan tubuh garis depan atau innate immunity; 2) menstimulasi produksi immunoglobulin IgM dan IgG di dalam sirkulasi; 3) memblokir agar virus tidak terikat oleh receptor ACE-2; 4) menurunkan intensitas badai sitokin; 5) menurunkan kecepatan replikasi virus.